Bridging the Worlds - Saari, Lise (Academy of Management Journal, 2007)
In this article the author comments on the article "The Very Separate Worlds of Academic and Practitioner Periodicals in Human Resource Management: Implications for Evidence-Based Management," by Sara L. Rynes, Tamara L. Giluk and Kenneth G. Brown, which appears in this edition of the journal. She notes the finding made in the article that trade publications pay little heed to the academic research available in scholarly periodicals. The author suggests that academic researchers bear in mind issues of most importance to managers, such as the value of effective hiring practices and the ways in which personnel management can influence an organizations rate of return, sales and profits.